2013
DOI: 10.1136/bmjopen-2013-003499
|View full text |Cite
|
Sign up to set email alerts
|

Loss to follow-up occurs at all stages in the diagnostic and follow-up period among HIV-infected patients in Guinea-Bissau: a 7-year retrospective cohort study

Abstract: ObjectivesTo describe loss to follow-up (LTFU) at all stages of the HIV programme.DesignA retrospective cohort study.SettingThe HIV clinic at Hospital National Simão Mendes in Bissau, Guinea-Bissau.ParticipantsA total of 4080 HIV-infected patients.Outcome measuresBaseline characteristics, percentages and incidence rates of LTFU as well as LTFU risk factors at four different stages: immediately after HIV diagnosis (stage 1), after the first CD4 cell count and before a follow-up consultation (stage 2), after a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
60
6
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 39 publications
24
60
6
3
Order By: Relevance
“…When compared to findings elsewhere in Ethiopia, discontinuation rate in the current study was higher than findings from the Tigray’s study [14] and lower than findings from the Amhara’s study [15]. In addition, this rate was lower than findings from studies conducted in Guinea-Bissau (51.1%)[39], Nigeria (28%)[40], and a multi-clinic study from Republic of Congo, Cameron and Burundi (83%)[41]. The dissimilarity in measurement[42], access to HIV care services[43], and innovation, adoption and implementation of cost-effective retention strategies could be the possible reasons of differences[44, 45].…”
Section: Discussioncontrasting
confidence: 84%
“…When compared to findings elsewhere in Ethiopia, discontinuation rate in the current study was higher than findings from the Tigray’s study [14] and lower than findings from the Amhara’s study [15]. In addition, this rate was lower than findings from studies conducted in Guinea-Bissau (51.1%)[39], Nigeria (28%)[40], and a multi-clinic study from Republic of Congo, Cameron and Burundi (83%)[41]. The dissimilarity in measurement[42], access to HIV care services[43], and innovation, adoption and implementation of cost-effective retention strategies could be the possible reasons of differences[44, 45].…”
Section: Discussioncontrasting
confidence: 84%
“…This lack probably led to an underestimation of the prevalence of treatment failure since patients for whom failure was not assessable may be a subgroup with poor healthcare-seeking behaviour. The HIV clinic in Bissau has a high rate of LTFU [9], and mortality may have been underestimated because some of the patients classified as LTFU may have in fact died [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients on ART were considered lost to follow-up (LTFU) if they had not visited the clinic for six months. Information on death and transfer to other ART centres was collected by personal information, telephone calls with contact persons or from the hospital wards [9]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies in high-income countries have demonstrated increased risk of mortality among HIV-infected persons living below the poverty line 4 and in neighborhoods with lower average annual income, 5 though the latter relationship was largely accounted for by differential access to antiretroviral therapy (ART). In addition to mortality, LTFU has emerged as a key outcome in HIV treatment given the high rates of LTFU across stages 6 of clinic enrollment, pre-ART evaluation, and ART adherence observed in SSA 79 . To the best of our knowledge, studies evaluating the relationship between SES and long-term mortality or LTFU have not been replicated in Sub-Saharan Africa (SSA).…”
Section: Introductionmentioning
confidence: 99%